Preparation and thermal behavior of mixture of basic carbonate and 4-dimethylaminocinnamylidenepyruvate with lanthanides (III) and yttrium (III) in the solid state - Leles, MIG; Melios, C. B.; D'Assuncao, L. M.; Ionashiro, Massao [UNESP] (Editora Unesp, 1999)
Solid Ln-OKCO3-DMCP compounds, where Ln represents lanthanides (III) and yttrium (III) ions and DMCP is the anion 4-dimethyiaminocinnamylidenepyruvate, have been prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and elemental analysis have been used to characterize the compounds. The thermal stability as well as the thermal decomposition of these compounds were studied using an alumina crucible in an air atmosphere.
Keywords: basic carbonate-4-dimethylaminocinnamylidenepyruvate; lanthanides; thermal behavior